Financial Planning PT. Luxury Indah Jaya “Premium Laundry Services” - Thomas Hadinata; Havidz Aima; Tantri Yanuar Rahmat Syah (Journal of Social Science, 2023)
One of the tourism industries that contributes to national development is the hotel industry. The hotel business can support other businesses, whether it is the right place to hold meetings or cooperation agreements, it can also be a place to increase human resource competency through training. The hotel is also a means for family gatherings to relieve fatigue, a place to stay for delegations from fellow countries at state meetings. The existence of a hotel must of course be accompanied by excellent service, including cleanliness and quality of towels and linen for its guests. The presence of a laundry business service that serves hotel needs is very much needed. This business plan offers a premium laundry service specifically for 4 and 5 star hotels. PT. Luxury Indah Jaya (Luxury Laundry) not only offers towel and linen laundry services but also provides towel and linen rental and guarantees the availability of hotel needs. Luxury Laundry has an IFE score of 2.90 and an EFE score of 3.02, where Luxury Laundry's competitive strength is in the medium category based on the results of the Five Forces Portes Model analysis. Luxury Laundry's financial plan is prepared by considering capital requirements and all costs in running a business company. This research aims to analyze Luxury Laundry's financial planning. The method used in this research is qualitative analysis.